KEDUDUKAN ORGANISASI INTERNASIONAL DALAM MAHKAMAH INTERNASIONAL - Fitriati, Vici; Manik Pinatih, SLP. Dawisni (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
This paper entitled “The position of international organizations on International Court of Justice”. International Court of Justice is a primary organ of United Nations which exist from 1946, a year after the establishment of The United Nations, to solve a legal problem between states. International Court of Justice is an improvement from International Permanent Court of Justice which formed by the League of Nations. The research method that used in this paper is the normative legal research, which use a secondary resources. The issue on this paper are, is the international organizations has a capability to litigants in International Court of Justice, and what kind of legal action can be done by international organizations in solving international problems it faces.
Keywords: International Organizations, International Court of Justice, Advisory Opinion